Expression of Prototype Foamy Virus Pol as a Gag-Pol Fusion Protein Does Not Change the Timing of Reverse Transcription - Jackson, Dana L. (American Society for Microbiology, 2013)
Foamy viruses are retroviruses whose Pol protein is synthesized without Gag from a spliced mRNA. Unlike orthoretroviruses, reverse transcription occurs during viral assembly, leading to DNA-containing virions. When prototype foamy virus Pol is expressed as an orthoretroviral-like Gag-Pol fusion protein, reverse transcription also occurs late in viral replication, as measured by the timing of reverse transcriptase sensitivity to the inhibitor 3′-azido-3′deoxythymidine (AZT). Thus, timing of reverse transcription is intrinsic to Pol itself.